Farm to School of Park County : a journey from program to Nonprofit (D) - Cates, Karen L., (SAGE Business Cases., 2019)
The final case in a four case series, the Farm to School organization has just issued its first annual report, filled with meaningful accomplishments. The leaders of the organization begin to plan to build an organization that will outlast them and the founding board members.